Dadung Feast Rite As A Cultural Expression in Legok Herang Village, Kuningan district - Retnawati, Nina; Wastap, Jaeni B; Saleh, Sukmawati (Pascasarjana ISBI Bandung, 2023)
This research aims to examine the tradition of the Dadung Party in Legokherang village, Kuningan Regency, West Java. A tradition that expresses gratitude to God for the harvest and the entity maintaining the relationship between living creatures and nature. The research method used is qualitative with a dance anthropology approach which is elaborated with choreographic concepts. This research shows that the Dadung Party is an integral part of community life and has been passed down from generation to generation. It also has connections to the Islamic beliefs propagated by the Wali Songo. This ritual involves various stages, such as worship, Rajah Pamunah, and entertainment and ritual equipment that must be adhered to by community participants. This tradition is a preserved cultural heritage and functions as a balance to modern culture. The noble philosophical values contained in the dance at the Dadung Party although this dance does not have fixed movements, the emphasis on expression as a manifestation of feelings is very important. Local cultural continuity is a dynamic part of society, and external cultural influences must be adapted to the worldview and local culture.